Foodborne disease in Kenya: The case for greater public investment - Hoffmann, Vivian; Baral, S. (International Food Policy Research Institute, 2020)
Infographic created for Voice for Change Partnership, Food and Nutrition Security Dissemination Forum: Evidence for Policy, Advocacy and Partnerships, Online Webinar, 8th July 2020.